Analysis of dam deformation with robust weight functions - Berkant Konakoğlu (Geodetski Vestnik, 2020)
Civil engineering structures (e.g., bridges, dams) are exposed to deformation under the influence of various factors such as water level changes, landslides, tectonic phenomena, etc. These deformations must be periodically monitored. Various deformation analysis approaches have been developed to describe the behaviour of a structure or natural process. The most significant task in deformation analysis is to correctly classify whether the points are stable or unstable. In this study, various robust weight functions for determination of stable/unstable points were applied to the Deriner Dam using GNSS (Global Navigation Satellite System) data measured over four different periods. The robust weight functions examined included the Andrews, Beaton−Tukey, Cauchy, Danish, Fair, German−McClure, Hampel, Huber, L1, and L1−L2. Test results were evaluated, and the performances of the different deformation analysis methods were determined. It was concluded that the horizontal deformations based on GNSS data determined by these robust weight functions were in good agreement with each other, except for the L1−L2. The results of all approaches were also compared with the results of the θ^2–Criteria method. According to the results obtained, although the θ^2–Criteria and the robust methods yielded nearly similar results, the results of the θ^2–Criteria method were thought to be more reliable.